2018
DOI: 10.1108/ijbm-05-2017-0082
|View full text |Cite
|
Sign up to set email alerts
|

Intention to use e-banking services in the Jordanian commercial banks

Abstract: Purpose The purpose of this paper is to investigate the essential factors influencing the adoption and use of e-banking services as perceived by customers of the Jordanian commercial banks. Design/methodology/approach This paper adapts and modifies the unified theory of acceptance and use of the technology model. Modifications were made to explain intention to use e-banking services. Findings The modified model explained 0.887 of behavior intention variance and 0.516 percent of the intended degree of e-ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 65 publications
(84 reference statements)
5
70
1
4
Order By: Relevance
“…They get financial benefits and time benefits because when they carry out transactions they no longer need to spend money and to spend time going to the bank or ATM which sometimes requires queues. The findings are in agreement with the outcome of a study steered by Adapa andRoy (2017), Sánchez-Torres et al, (2018), Yaseen and El Qirem (2018). Besides that, they only need very little time to carry out each transaction.…”
Section: Results and Discussion 41 Benefits Of Internet Bankingsupporting
confidence: 90%
“…They get financial benefits and time benefits because when they carry out transactions they no longer need to spend money and to spend time going to the bank or ATM which sometimes requires queues. The findings are in agreement with the outcome of a study steered by Adapa andRoy (2017), Sánchez-Torres et al, (2018), Yaseen and El Qirem (2018). Besides that, they only need very little time to carry out each transaction.…”
Section: Results and Discussion 41 Benefits Of Internet Bankingsupporting
confidence: 90%
“…Social influence is defined as the degree to which an individual perceives the importance of the beliefs of others that he or she should use the new system (Venkatesh et al 2003;Yaseen and El Qirem 2018).…”
Section: Referencesmentioning
confidence: 99%
“…Performance Expectancy is defined as the degree to which an individual believes that using the system will help him/her to attain gain in job performance (Venkatesh et al, 2003;Zhang et al, 2018). In contrast, Yaseen and El Qirem (2018) found that Performance expectancy and hedonic motivation are not significant predictors. Effort Expectancy is defined as the degree of ease associated with the use of the system (Venkatesh et al, 2003;Warsame & Ireri, 2018;Wang et al, 2017).…”
Section: Yadgar Taha M Hamakhanmentioning
confidence: 95%
“…Social Influence is defined as the degree to which an individual perceives the importance of the beliefs of others on whether he or she should use the new system (Venkateshet al, 2003;Yaseen & El Qirem, 2018).…”
Section: Yadgar Taha M Hamakhanmentioning
confidence: 99%